STRATEGI KOMUNIKASI UNIT TRANSFUSI DARAH PMI KOTA PEKANBARU DALAM MENINGKATKAN JUMLAH KEBUTUHAN KANTONG DONOR DARAH - Yovan Rangkuti Sabda; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Blood donation is the process of donating blood by humans. This donation process is the taking of blood from one's body voluntarily to be used for others who need it. The Indonesian Red Cross is present as an agency that bridges blood donor activities, UTD is one of the sub-sections of PMI in charge of land transfusion services. Data for UTD PMI Pekanbaru City blood bags in 2019 were 50,688 bags, then in 2020 as many as 48,084, and in 2021 as many as 54,648. The existence of a significant increase after experiencing a decrease is what is considered interesting in this study. Researchers want to see how communication strategies play a role in increasing the data. This study uses a qualitative approach with descriptive analysis. The subject of the study was the UTD PMI Pekanbaru City administrator. The object under study is a communication strategy. This study ususesata collection techniques of observation, interviews, and documentation. To achieve the validity of the data in this study, the authors used data triangulation. The results of the study are described in several parts which include: communicator selection strategy is carried out with 3 indicators, namely credibility, attractiveness, and strength. The audience is determined by looking at the sociodemographic aspect, namely age as a benchmark and the support group being the group that plays the biggest role. The arrangement of messages is formed by involving the nature of informative, persuasivee and educating. The media selection strategy used is electronic media, new media, public media channels, and interpersonal communication channels. The socialization carried out by UTD used the concept of secondary, participatory, formal, and direct. The obstacles found were in the form of a pandemic situation that hindered the movement of the UTD. Keywords: Communication Strategy, PMI, Blood Donation Bag